(untitled) (MATEMATIKA, 2013)
Most researchers today prefer to use Bezier curve in their works rather than Beta-spline curve. There are several reasons and one of them is that Bezier curve is faster to plot than Beta-spline. However Beta-spline also has several advantages and one of it is this curve is built on G^2 continuity condition. This property makes Beta-spline achieves the required smoothness faster than Bezier curve. In this paper, we introduce the method of Beta-spline control points evaluation and make comparison between Bezier and Beta-spline curves in terms of their continuity, and circle approximation. Keywords: Bezier; Beta-spline; Circle approximation; Control points evaluation 2010 Mathematics Subject Classification: 65D07